2023
DOI: 10.1002/inf2.12419
|View full text |Cite
|
Sign up to set email alerts
|

Robust hydrogel sensors for unsupervised learning enabled sign‐to‐verbal translation

Abstract: Highly stretchable and robust strain sensors are rapidly emerging as promising candidates for a diverse of wearable electronics. The main challenge for the practical application of wearable electronics is the energy consumption and device aging. Energy consumption mainly depends on the conductivity of the sensor, and it is a key factor in determining device aging. Here, we design a liquid metal (LM)-embedded hydrogel as a sensing material to overcome the barrier of energy consumption and device aging of wearab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 58 publications
(76 reference statements)
0
14
0
Order By: Relevance
“…Researchers have attempted to transform sign language into recognizable signals to facilitate online communication for deaf people. Strain sensors are usually used to capture the response signals generated by the bending of different fingers to represent the letters in sign language. However, it is not possible to recognize all the sign language gestures by the response signals of finger bending alone; for example, the sign language gestures representing the letters C, E, O, and S all require the bending of five fingers, which results in the same response signals for these gestures. Analyzing the sign language gestures, we found that the sign language gestures representing the 26 letters of the alphabet can be fully recognized by the difference in the response signals captured by the sensors for finger bending and fingertip pressing.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Researchers have attempted to transform sign language into recognizable signals to facilitate online communication for deaf people. Strain sensors are usually used to capture the response signals generated by the bending of different fingers to represent the letters in sign language. However, it is not possible to recognize all the sign language gestures by the response signals of finger bending alone; for example, the sign language gestures representing the letters C, E, O, and S all require the bending of five fingers, which results in the same response signals for these gestures. Analyzing the sign language gestures, we found that the sign language gestures representing the 26 letters of the alphabet can be fully recognized by the difference in the response signals captured by the sensors for finger bending and fingertip pressing.…”
Section: Results and Discussionmentioning
confidence: 99%
“…7d and e). 166 This system provides an ideal strategy for achieving communication between deaf and normal people and broadening the application of wearable electronics.…”
Section: Applications Of Lm–hydrogel Compositesmentioning
confidence: 99%
“…Examples include epidermal, wearable, and implantable bioelectronics. These devices enable continuous, noninvasive monitoring of vital physiological signals in real time, comfortably providing clinically relevant information for disease diagnosis, preventive healthcare, and rehabilitation. These devices are particularly promising for managing chronic diseases like cardiovascular issues, metabolic disorders, and diabetes, which are of significant in an aging population. During health crises like the COVID-19 pandemic, they can reduce the need for hospital visits and readmissions . Beyond bioelectronics, the versatility of flexible electronics extends to wearable energy harvesters, robotic skins for haptic interfaces, and smart skins for aircraft to measure aerodynamic parameters in situ . The trend towards flexible electronics is also evident in fields like photonics, acoustics, , metamaterials, and etc. These devices are ultrathin, low-modulus, and lightweight, making them “mechanically invisible” when applied to objects with arbitrary surfaces. …”
Section: Introductionmentioning
confidence: 99%